Antibody Responses to Meningococcal Polysaccharide Vaccines - Brandt, Brenda L. (1973)
Over the past 4 years 19 lots of group C polysaccharide vaccine and five lots of group A polysaccharide vaccine have been tested for their immunogenicity in man. For each lot tested, groups of 18 to 50 men received 50 μg of vaccine subcutaneously. Sera were obtained prior to and 2 weeks after vaccination. The analytical and serological methods used in these studies were Sepharose 4B chromatography for the estimation of molecular size, the radioactive antigen binding assay, and the indirect hemagglutination (IHA) test for measuring the antibody response. Results have shown that the radioactive antigen binding assay is preferable to the IHA test as a measure of antibody response. Group C meningococcal vaccines have been highly stable when stored at 4 C in powdered form. All lots of group C vaccine tested to date have been of equal potency, with molecular weight varying from 520,000 to 2,000,000. Group A polysaccharides have been found to be unstable after 2 years of storage at 4 C. Optimal antibody response to the group A vaccines appears to be directly related to the molecular size of the preparation.